An Artifact Ecology in a Nutshell: A Distributed Cognition Perspective for Collaboration and Coordination - Vasiliou, Christina; Ioannou, Andri; Zaphiris, Panayiotis (My University, 2015)
An artifact ecology is an environment where multiple heterogeneous technologies co-exist and are interlinked as a unified system. To construct effective ecologies of artifacts for collaborative activities we need to acquire deep understanding of the complex interactions and interdependencies between users and tools. Researchers have identified Distributed Cognition (DC) as a powerful tool for understanding these interdependencies. In this study, DC, and particularly the DiCoT framework, were considered ideal for constructing this understanding for four student-groups during collaborative activities in an artifact ecology. Using DiCoT we analysed learners’ behaviour and how the artifact ecology supported collaboration and cooperation. The cognitive system was described from three different perspectives - physical layout, information flow and artifacts - which (i) allowed an in-depth understanding of the interactions among learners and tools during collaborative activities and (ii) provided insights on how the affordances of the artifact ecology supported collaboration and coordination.
Keywords: Distributed cognition; DiCoT framework; Artifact ecology; Technology-rich workspace; HCI education; Collaboration; Coordination